1981
DOI: 10.1111/j.1600-0587.1981.tb00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns and food habits of Baetis rhodani, Capnia pygmaea and Diura nanseni in a West Norwegian river

Abstract: As a part of weir‐pond‐ecosystem project, the growth patterns and food habits of Baetis rhodani (Ephemeroptera), Capnia pygmaea (Plecoptera), and Diura nanseni (Plecoptera) were investigated. B. rhodani was bivoltine. The winter generation consisted of three cohorts. C. pygmaea and D. nanseni accomplished their nymphal growth in one year. The predominate food consumed by B. rhodani and C. pygmaea was detritus. Variations in the diet of these detritivores are discussed in relation to microdistribution and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…These are in conformity with the observations of some previous workers. Studies of Badcock (1949), Brown (1961) and Baekken (1981) on Baetis rhodani and of Gupta and Michael (1981) on Baetis sp. in Shillong, Meghalaya revealed them to be mainly detritivorous whereas Brown (1960) has shown that several species of algae were thoroughly and rapidly digested by Cloeon dipterum in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are in conformity with the observations of some previous workers. Studies of Badcock (1949), Brown (1961) and Baekken (1981) on Baetis rhodani and of Gupta and Michael (1981) on Baetis sp. in Shillong, Meghalaya revealed them to be mainly detritivorous whereas Brown (1960) has shown that several species of algae were thoroughly and rapidly digested by Cloeon dipterum in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Notable publications in this direction include those of Johansson (1958), Slansky (l980a, b), Ananthakrishnan et al (1982) and Raman and Sanjayan (1983). Whereas there are some investigations on feeding propensities (Brown 1960(Brown , 1961Gupta and Michael 1981;Venkataraman 1984), food habits (Baekken 1981), trophic relations (Winterbourn 1974), food preference and dependence of growth on the type of food (Cianciara 1980) and nutritional dynamics (Zimmerman and Wissing 1980), work on the impact of nutrition on reproduction of mayflies is conspicuous by its absence. The present investigation aims at understanding and comparing the feeding propensities, growth rate and fecundity of two species of Baetis and one species of Cloeon available in and around Madurai, based on laboratory observations.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters:k E = 18.6 (sd 0. 37 individuals over the i-state. Individuals with almost identical i-states are thus taken together in a cohort, and counted.…”
Section: Structured Populationsmentioning
confidence: 99%
“…The pointed shifts in diet composition among size classes could result in considerable changes in microhabitats, enabling a different habitat choice among the different size classes of both species, as noted by BAEKKEN (1981) for other mayflies. BAEKKEN (1981) thought this could reduce the interaction between nymphal stages within the same species and between two coexisting detritivores species, as seems to be the case in our study. This explanation could be also applied for interpreting the existence of a great range in nymphal size (ARNEKLEIV, 1996), as we found in our study.…”
Section: Final Remarksmentioning
confidence: 74%